“Where exactly do I fall?”: understanding intersectional marginalized identities through Asian Americans’ experiences - Zhang, Bin; Du, Wenqian; Chang, Bo (Frontiers in Psychology, 2024)
The purpose of this study is to understand the intersection of race, gender, and sexual orientation through exploring the experiences of Asian American female sexual minority (AAFSM) college students in the U.S. Midwestern universities. We employed one of McCall’s three intersectionality methodological approaches—intra-categorical complexity—to guide the study. The findings indicated that the AAFSM student participants had experienced intersectional objectifications, including racial, gendered, and sexual objectification. The finding answered our research question regarding what it is like to be AAFSM students attending predominantly White campuses in Midwestern universities. Our findings also showed that the participants intersectionally internalized racism, sexism, and heterosexism as strategies to avoid being ostracized, which in turn allowed society/institution to internalize these -isms as norms. The manifestations of intersectional internalizations reported by participants included racial stereotypes, Whitenization, stereotypical gender roles, gender norms, parental influence, and institutional influence. The findings also indicated that the participants experienced intersectional blindness, which affected their understanding of Asianness, womenness, and LGBTQness. Another meaningful finding was that the racism, sexism, and heterosexism experiences of the AAFSM students were compounded and complex. The theme was best categorized as intersectional post-racism-(hetero)sexism. We discussed intersectional internalization; de-intersectional-internalization; re-intersectional-internalization; intersectional visibilities, connections, and representations; the implementation of intersectionality; and intersectionalism. The discussions, as a milestone, provided meaningful suggestions for educators, administrators, and universities to effectively create an intersectional inclusive educational environment for AAFSMs.